(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Hylocereus species or better known as dragon fruit or pitaya from the Cactaceae family had become interest subject to many researchers mainly due to its unique taste, shape and the flesh colour. The functionality of H. polyrhizus seed are including antioxidant property and the uses of different part of H. undatus in promoting wound healing in diabetic rats also have been reported. Therefore the present study was aimed to investigate the active phytochemical constituents of ethanol, chloroform and hexane extracts from H. undatus peel. The findings obtained in the study could support the potential application of pitaya peels as a natural source of various active chemical constituents with relation to its potential health benefit in providing perspectives of research and application.